2009
DOI: 10.1016/j.pbb.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin potentiates the antidepressant efficacy of fluoxetine in rats

Abstract: Background-Cholesterol may have a role in the pathophysiology of depression. Lowering cholesterol levels with statins reduces risks for cardiovascular events, and there is clinical evidence that statins exert neuroprotective properties not fully explained by their effects on serum cholesterol levels. Altered cholesterol levels can affect serotonergic neurotransmission, which might be involved in the clinical efficacy of standard antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Similarly, the affinity of RTI-55 appears to be unaffected by cholesterol depletion similar to what has been shown for CFT affinity for DAT (12). However, the inhibitor, cocaine, has been shown to induce a more outward-facing conformation than imipramine (28) (40), augmented fluoxetine efficacy (41). Also, roles for both cholesterol and sphingolipid homeostasis in psychiatric disorders have been noted (42,43).…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, the affinity of RTI-55 appears to be unaffected by cholesterol depletion similar to what has been shown for CFT affinity for DAT (12). However, the inhibitor, cocaine, has been shown to induce a more outward-facing conformation than imipramine (28) (40), augmented fluoxetine efficacy (41). Also, roles for both cholesterol and sphingolipid homeostasis in psychiatric disorders have been noted (42,43).…”
Section: Discussionmentioning
confidence: 59%
“…However, one of the findings, combination of lovastatin with low dose of fluoxetine augments antidepressant-like effect. As indicated by decreased immobility and accelerated swimming among rats, lovastatin increases the antidepressant efficacy of fluoxetine in laboratory animals, [22] and the action of lovastatin may involve the serotonergic instead of noradrenergic pathways, confirming augmentation of serotonergic function by statins. The reduction in immobility time by atorvastatin in our experiment may be due to increased activity in blocking the noradrenaline uptake.…”
Section: Discussionmentioning
confidence: 85%
“…These results are consistent with one previous study wherein lovastatin potentiated antidepressant effects of fluoxetine only in chronic FST. 16 Open field test is usually performed to discriminate between the general behavioral stimulation (false positives) and antidepressant effect of study drugs. The OFT study showed no significant difference in the frequency of line crossings, rearings and defecation among all the groups.…”
Section: Discussionmentioning
confidence: 99%
“…8 There is evidence from animal studies that Lovastatin can augment the antidepressant effects of a low dose of fluoxetine in rats, raising the possibility that statins could be used to facilitate the effects of antidepressants in humans. 9 However, the literature search revealed lack of sufficient data either from animal studies or clinical trials related to the antidepressant activity of statins. Hence present experimental study has been designed to evaluate antidepressant activity of simvastatin from the group of available statins.…”
Section: Introductionmentioning
confidence: 99%